2018
DOI: 10.1136/bmjopen-2017-020037
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and publication fate of unregistered and retrospectively registered clinical trials submitted toThe BMJover 4 years

Abstract: ObjectivesWe sought to evaluate the characteristics and publication fate of improperly registered clinical trials submitted to a medical journal (The BMJ) over a 4-year period to identify common types of registration issues and their relation to publication outcomes.DesignResearch articles submitted to The BMJ and identified as unregistered or retrospectively registered by editors were included if they reported outcomes of a clinical trial. Relevant data regarding the trials were then extracted from each paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 11 publications
0
39
0
Order By: Relevance
“…Another reason for the difference is that we included trials registered in other registries and that practices with regard to prospective registration might be different among trials registered in these. Lastly, among 123 trials rejected by the BMJ between June 2013 and June 2017 because they did not comply with ICMJE trial registration requirements, 89% were retrospectively registered and 7% were unregistered [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another reason for the difference is that we included trials registered in other registries and that practices with regard to prospective registration might be different among trials registered in these. Lastly, among 123 trials rejected by the BMJ between June 2013 and June 2017 because they did not comply with ICMJE trial registration requirements, 89% were retrospectively registered and 7% were unregistered [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that although ICMJE guidance recommends that journals should not publish manuscripts from trials that were not registered or were retrospectively registered, such trials continue to be published in the medical literature, including in high-impact journals. 4 While compliance with ICMJE registration has been investigated in individual specialities such as cardiology 5,6 , no studies to date have reported on adherence to the ICMJE policy within respiratory medicine.…”
mentioning
confidence: 99%
“…Classification of trials followed a published approach used by the British Medical Journal. 4 Briefly, a trial was considered to be registered if the publication included a registration number of an acceptable primary registry -one belonging to the WHO International Clinical Trials Registry Platform (ICTRP). If no registration number was reported in the publication, the trial was searched for using the ICTRP search platform.…”
mentioning
confidence: 99%
“…Clinicaltrials.gov originally encouraged registration for trials that dealt with serious illness. This position was expanded when The International Committee of Medical Journal Editors (ICMJE) announced in 2005 that their journals would no longer publish reports of trials unless they were prospectively registered in a trial registry that met the quality standards recommended by the World Health Organization (73). The risk of selective reporting remains a threat in 2017 where approximately one third of trials listed in ClinicalTrials.gov were registered three months following participant enrollment and of these, fifty percent were not registered within the first 12 months (74).…”
Section: Study Limitationsmentioning
confidence: 99%